MDM2 promoter del1518 polymorphism and cancer risk: evidence from 22,931 subjects - Hua, Wenfeng; Zhang, Anqi; Duan, Ping; Zhu, Jinhong; Zhao, Yuan; He, Jing; Zhang, Zhi (OncoTargets and therapy, 2017)
Studies have shown that single-nucleotide polymorphisms in gene may play important roles in the development of malignant tumor. The association of del1518 polymorphism (rs3730485) in the promoter with cancer susceptibility has been extensively studied; however, the results are contradictory. To quantify the association between this polymorphism and overall cancer risk, we conducted a meta-analysis with 12,905 cases and 10,026 controls from 16 eligible studies retrieved from PubMed, Embase, and Chinese Biomedical (CBM) databases. We assessed the strength of the connection using odds ratios (ORs) and 95% confidence intervals (CIs). In summary, no significant associations were discovered between the del1518 polymorphism and overall cancer risk (Del/Del vs Ins/Ins: OR =1.01, 95% CI =0.90-1.14; Ins/Del vs Ins/Ins: OR =1.03, 95% CI =0.96-1.12; recessive model: OR =0.98, 95% CI =0.90-1.07; dominant model: OR =1.03, 95% CI =0.94-1.12; and Del vs Ins: OR =1.01, 95% CI =0.94-1.07). In the stratified analysis by source of control, quality score, cancer type, and ethnicity, no significant associations were found. Despite some limitations, the current meta-analysis provides solid statistical evidence of lacking association between the del1518 polymorphism and cancer risk.